Unification of Therapeutic Activities on the Example of Pedagogical Innovation "Together, You can do More. I help Myself "- an Attempt to Conceptualize the Coupling of Therapeutic Methods in the Aspect of Working with an Autistic Student - Morgała, Monika Bożena; Grzyb, Barbara; Pituła, Beata (Studia Warmińskie, 2019)
The specificity and determinants associated with the work of teachers and therapists of people with disabilities, as well as expectations and increasing demands from both legislators and families, cause the necessity of permanent development. In the context of the changing approach to pedagogical and therapeutic work, it is essential to look for innovative solutions. This applies not only to the competences of educators, but also to the searching and broadening process of educational and therapeutic interactions with new, sometimes controversial, methods and forms of work. The authors of the article have tried to summarize the implemented pedagogical innovation entitled "Together, you can do more. I help myself " in the Cluster of Schools and Revalidation and Education Institution in Wodzisław Śląski, Upper Silesia. Innovation has been carried out in the group of children with autism. The intention of the creators of the text is to demonstrate the effectiveness of combining the Elements of Bibliotherapy and the Sherborne Developmental Movement method (SDM) in the therapeutic process. Due to the results of the research, the authors would like to point out the rightness of undertaking activities related to the implementation of an innovative solution which is an attempt to couple various therapeutic methods in the aspect of working with an autistic students.